Data compression and genomes: A two-dimensional life domain map - Menconi, Giulia; Benci, Vieri; Buiatti, Marcello (Journal of theoretical biology, 2008)
We define the complexity of DNA sequences as the information content per nucleotide, calculated by means of some Lempel–Ziv data compression algorithm. It is possible to use the statistics of the complexity values of the functional regions of different complete genomes to distinguish among genomes of different domains of life (Archaea, Bacteria and Eukarya). We shall focus on the distribution function of the complexity of non-coding regions. We show that the three domains may be plotted in separate regions within the two-dimensional space where the axes are the skewness coefficient and the curtosis coefficient of the aforementioned distribution. Preliminary results on 15 genomes are introduced.